2021
DOI: 10.12669/pjms.37.2.3422
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception and scores in Paediatrics end-of-clerkship and final professional Objective Structured Clinical Examination (OSCE): A comparative study

Abstract: Objectives: This study aims to understand students’ perception of the usefulness of end-of-clerkship (EOC) as compared to professional exam Objective Structured Clinical Examinations (OSCE) and to compare student performance in both examinations. Methods: We conducted a cross-sectional study of medical students who were studying in the final year at Shifa College of Medicine, Shifa Tameer-e-Millat University, and appeared in both end-of-clerkship and final professional exams. The study was conducted in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
7
0
3
Order By: Relevance
“…believe that one of the proper evaluation methods to assess the clinical skills of the students is the OSCE method which has appropriate criteria for clinical evaluation of the students. [ 29 30 31 ] The results of the study by Gandomkar and Amini also showed that among the clinical skills evaluation tests, OSCE test is the most used test in the clinical medical courses in Iran. [ 32 33 34 ] Results of the study by Rafiee et al .…”
Section: Discussionmentioning
confidence: 99%
“…believe that one of the proper evaluation methods to assess the clinical skills of the students is the OSCE method which has appropriate criteria for clinical evaluation of the students. [ 29 30 31 ] The results of the study by Gandomkar and Amini also showed that among the clinical skills evaluation tests, OSCE test is the most used test in the clinical medical courses in Iran. [ 32 33 34 ] Results of the study by Rafiee et al .…”
Section: Discussionmentioning
confidence: 99%
“…"*' + ',( -% ," % ,% -#&.' -% /,+ 0 -0% ) % 1 .% -',( +63304.% ( -% 2 42 4 3456789: 4<= = > 9<?48@ 8: A 49> 5<789: 8B4ACDE DFGIJK LDMNGK OFMPGQR E SGTGK JUTK JV DM M JK W GXPJ NGLR M Y ZK R JQ[\DK R JK U87]^_ `a_ b`b]Uc=]de ]fU549g 4A 78h4A iA > 44j5> <@?8kA <= l @ > <U547g 69?<789: 4 94<A : mnoUp]oU?4385A 8: 49odm q^aU?8d?846: 6rA 4?8b`]qm 3456789: 4<= = > 9<?48@ 8: A 49> 5<789: 8B4AsJM R tuKvE SDMw[DK R FJUxM [uK R JyzY DK FJU87]^_ `a_ b`b]U c=]de b`U549g 4A 78h4A iA > 44j5> <@?8kA <= l @ > <U547g 69?<789: 494<A : mnoUp]oU?4385A 8: 49odm q^aU ?8d?846: 6rA 4?8b`]qm 3456789: 4<= = > 9<?48@ 8: A 49> 5<789: 8B4A{ [E R GFGTDK DR K GPGQR E SG|G}[R tUTK JV DM M JK W GXPJyFM R FJ IuM R ~JZ~FR ~JDD~FJE LR ~JU87]^_ `a_ b`b]Uc=]de b`U549g 4A 78h4A iA > 44j5> <@?8kA <= l @ > <U547 g 69?<789: 494<A : mnoUp]oU?4385A 8: 49odm q^aU?8d?846: 6rA 4?8b`]qm 3456789: 4<= = > 9<?48@ 8: A 49> 5<789: 8B4AGFDM M GIDGY K R NJFY DR K JGE GM M RQ\R FR UTK JV DM M JK W GXPJ NGLR M Y ZK R JQ[\DK R JK U87]^_ `a_ b`b]Uc=]de ^aU549g 4A 78h4A iA > 44j5> <@?8kA <= l @ > <U547g 69?<789: 4 94<A : mnoUp]oU?4385A 8: 49odm q^aU?8d?846: 6rA 4?8b`]qm 3456789: 4<= = > 9<?48@ 8: A 49> 5<789: 8B4AsyvvsCvIvssy vvUxM [uK R JyzY DK FJU87 ]n_ `a_ b`b]Uc=]be bqU549g 4A 78h4A iA > 44j5> <@?8kA <= l @ > <U547g 69?<789: 494<A : mnoUp]oU?4 385A 8: 49odm q^aU?8d?846: 6rA 4?8b`]qm <6: 895> ?<?8?8= : 8?456789: 4B4?8= 8A549g 8A > ?<94= > : 8 hB= e _ _ m = 8> m 6g 6m rA _ = 8> _ 549: A 4@ <?4A 8: 8A 94m BhB <5<4?456789: 4549g 8A > A > ?4A <4<58= = 48: 8A 94`U> 9g 4A 7<9?445?> 48A > j5<?4A8 45?> 4|Im TERVO et al, 1997;CHISNALL;VINCE;TRIBE, 2015;LABAF et al, 2014;JOSHI et al, 2017;Chima, 2016;KHAN et al, 2021;SKINNER;NEWTON;CURTIS, 1997;JEFFERIES et al, 2007).…”
mentioning
confidence: 99%
“…No entanto, apesar de seu valor formativo e de sua contribuição para a consolidação de competências necessárias à formação profissional, muitos estudantes associam níveis aumentados de estresse e ansiedade em provas de demonstração de habilidades e atitudes, como o OSCE (KHAN et al, 2021;FERREIRA et al, 2020), o que acarretaria prejuízo no desempenho por conta dos sentimentos desencadeados.…”
unclassified
See 2 more Smart Citations